Influence of Exercise on Inferior Vena Cava Wall Interaction with Inferior Vena Cava Filters: Results of a Pilot In Vivo Porcine Study - M. Usman Shahid; Neel Nirgudkar; Vishnu Chandra; Sharon Gonzales; Abhishek Kumar (The Arab Journal of Interventional Radiology)
Objectives The aim of this study was to assess the effect of mild exercise on inferior vena cava (IVC) filter interaction with imaging and pathological features with the neighboring vessel wall utilizing a porcine model. Materials and Methods After Institutional Animal Care and Use Committee (IACUC) approval, retrievable Option Elite IVC filters were implanted in six Yorkshire pigs utilizing the right common femoral vein approach under general anesthesia. Group A (n = 4) pigs remained sedentary for 4 weeks. Group B (n = 2) pigs were exercised using a harness and treadmill for 10 minutes/day for 4 days/week. At approximately 4 weeks, IVC venograms were performed and the pigs were sacrificed. After laparotomy, the IVC was ligated above and below the filter, excised and fixed in formalin. Gross and histological examination of the IVC was performed. Gross images of each sample were captured before removal of the filters. One longitudinal, one tangential, and five transverse representative sections were processed for paraffin sectioning and hematoxylin and eosin slides were prepared. A pathologist examined all tissues to assess differences between normal vein, group A and group B pigs. The pathologist provided an overall assessment and representative images. Results All IVC filter implantations were technically successful without adverse effects. There was no incidence of caval thrombosis, filter strut fracture, or filter migration in either group. On gross pathological examination, IVC of the pigs in group B demonstrated more perivascular and mural fibrosis than those pigs in group A. Histopathological findings correlated with gross findings. Conclusions In this pilot study, there were no incidence of IVC filter strut fracture, penetration or IVC occlusion in sedentary or exercised pigs. However, there tended to be more perivascular and mural fibrosis on pathological examination of inferior vena cavas from exercised pigs. Further larger scale studies may employ the porcine model to further understand the role exercise may play on IVC filter and caval wall interaction.